2017
DOI: 10.1038/s41522-017-0040-3
|View full text |Cite|
|
Sign up to set email alerts
|

High-resolution bacterial 16S rRNA gene profile meta-analysis and biofilm status reveal common colorectal cancer consortia

Abstract: Colorectal cancer (CRC) remains the third most common cancer worldwide, with a growing incidence among young adults. Multiple studies have presented associations between the gut microbiome and CRC, suggesting a link with cancer risk. Although CRC microbiome studies continue to profile larger patient cohorts with increasingly economical and rapid DNA sequencing platforms, few common associations with CRC have been identified, in part due to limitations in taxonomic resolution and differences in analysis methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
280
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 268 publications
(301 citation statements)
references
References 73 publications
16
280
2
3
Order By: Relevance
“…They always present alongside the normal colon cells in the tumor microenvironment. Therefore, a co‐culture study was performed to stimulate the intermediate development of CRC . The group had reported deregulation of acrogranin, insulin‐like growth factor binding protein 6 (IGFBP6) and vimentin which were suggested as inducer proteins for tumor progression .…”
Section: The Secretome Studies Of Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…They always present alongside the normal colon cells in the tumor microenvironment. Therefore, a co‐culture study was performed to stimulate the intermediate development of CRC . The group had reported deregulation of acrogranin, insulin‐like growth factor binding protein 6 (IGFBP6) and vimentin which were suggested as inducer proteins for tumor progression .…”
Section: The Secretome Studies Of Colorectal Cancermentioning
confidence: 99%
“…Therefore, a co‐culture study was performed to stimulate the intermediate development of CRC . The group had reported deregulation of acrogranin, insulin‐like growth factor binding protein 6 (IGFBP6) and vimentin which were suggested as inducer proteins for tumor progression . In metastatic CRC, secretome studies had revealed more proteins that may be critical in metastatic events.…”
Section: The Secretome Studies Of Colorectal Cancermentioning
confidence: 99%
“…Recently, increased abundance of Fusobacterium nucleatum, Bacteroides fragilis, and Escherichia coli have been associated with human CRC [1][2][3] . These species are hypothesized to promote tumorigenesis and/or progression of CRC through up-regulation of oncogenes, modification of intestinal mucus, or damage to host DNA 2,4,5 . In addition to the mere presence or absence of putative carcinogenic bacteria in the gut, the spatial localization and physical interaction with host epithelial cells may be critically important.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the inner, striated mucus layer of the colon is largely sterile in healthy hosts 6 . Perturbations of this tightly regulated spatial organization have been linked to both inflammatory bowel diseases (IBD) and CRC [12][13][14][15] . Mucosa-associated bacterial biofilms are defined as microbial aggregates embedded within a polymeric matrix of both host and bacterial origin that directly contacts epithelial cells 14,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Chloroplast and mitochondrial contaminants were detected and filtered using the RDP classifier with a confidence threshold of 80%. High-quality 16S rRNA sequences were assigned to a high-resolution taxonomic lineage using Resphera Insight(Drewes et al, 2017). Functional gene content was inferred using PICRUSt(Langille et al, 2013).…”
mentioning
confidence: 99%